2023
DOI: 10.3389/fpubh.2023.1126503
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of out-of-hospital cardiac arrest is still based on quick activation of the chain of survival

Abstract: Background and goal of studyCardiopulmonary resuscitation (CPR) in prehospital care is a major reason for emergency medical service (EMS) dispatches. CPR outcome depends on various factors, such as bystander CPR and initial heart rhythm. Our aim was to investigate whether short-term outcomes such as the return of spontaneous circulation (ROSC) and hospital admission with spontaneous circulation differ depending on the location of the out-of-hospital cardiac arrest (OHCA). In addition, we assessed further aspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
(39 reference statements)
0
0
0
Order By: Relevance
“…This trend seems consistent with the findings from the North American population where, out of 12,930 evaluated OHCAs, 9564 occurred at home [27]. Interestingly, Borgstedt et al (2023) found that the incidence of return of spontaneous circulation (ROSC) did not vary significantly between public and non-public locations (p = 0.4). However, patients experiencing OHCA in public spaces were more frequently admitted to the hospital with spontaneous circulation (p = 0.011) [28].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This trend seems consistent with the findings from the North American population where, out of 12,930 evaluated OHCAs, 9564 occurred at home [27]. Interestingly, Borgstedt et al (2023) found that the incidence of return of spontaneous circulation (ROSC) did not vary significantly between public and non-public locations (p = 0.4). However, patients experiencing OHCA in public spaces were more frequently admitted to the hospital with spontaneous circulation (p = 0.011) [28].…”
Section: Discussionsupporting
confidence: 89%
“…One study reported that between 2014 and 2017, out of 12,073 cases, 723 EMS responses related to OHCA were analyzed. Shockable initial heart rhythm, defibrillation, and resuscitative efforts initiated by an emergency physician were found to significantly enhance the chances of a patient's successful admission to a hospital with spontaneous circulation [28]. This underlines the necessity for early recognition and intervention in OHCA cases.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The median time between activation and EMS arrival was 13 minutes. It is important to work on decreasing the response time of the AO for OHCA assistance, given that the condition under study is time-dependent; that is, the more timely the assistance and specific interventions, the higher the probability of ROSC and hence of improved survival, since after this time range the metabolic changes become incompatible with life (13,17,24,25).…”
Section: Discussionmentioning
confidence: 99%